Security issues in IoT enabled Health Monitoring - Sharma, Renu (International Journal of Computer Sciences and Engineering, 2025)
IoT (Internet of things) means to connect heterogeneous devices with internet. When devices are medical then it involves human is at stake. It isimportant to provide security as well as privacy to a human. It should not be like a person using such devices, can be controlled from anybody and from anywhere. In this paper various security threats are discussed which can be raised while using smart health monitoring.